The impact of COVID-19 pandemic on psoriasis patients, and their immunosuppressive treatment: a cross-sectional multicenter study from Turkey - Kartal, Selda Pelin; Celik, Gokcen; Yilmaz, Oguz; Oksum Solak, Eda; Demirbag Gul, Busra; Ustunbas, Tuba Kevser; Alpsoy, Erkan (Taylor & Francis Ltd, 2022)
Background Immunosuppressive therapy has been a great concern during the pandemic. This study aimed to evaluate the pandemic's impact on psoriasis patients treated with immunosuppressive drugs. Material and Methods The multicenter study was conducted in 14 tertiary dermatology centers. Demographic data, treatment status, disease course, and cases of COVID-19 were evaluated in patients with psoriasis using the immunosuppressive treatment. Results Of 1827 patients included, the drug adherence rate was 68.2%. Those receiving anti-interleukin (anti-IL) drugs were more likely to continue treatment than patients receiving conventional drugs (OR = 1.50, 95% CI, 1.181-1.895, p = .001). Disease worsening rate was 24.2% and drug dose reduction increased this rate 3.26 and drug withdrawal 8.71 times. Receiving anti-TNF or anti-IL drugs was associated with less disease worsening compared to conventional drugs (p = .038, p = .032; respectively). Drug withdrawal causes were 'unable to come' (39.6%), 'COVID concern' (25.3%), and 'physician's and patient's co-decision' (17.4%). Four patients had COVID-19 infection with mild symptoms. The incidence was 0.0022% while it was 0.0025% in the general population. Conclusion Our study shows that psoriasis patients using systemic immunosuppressive do not have a higher, but even lower COVID-19 risk than the general population, and treatment compliance with biological drugs is higher.
Keywords: COVID-19; psoriasis; immunosuppressive drugs; biologics; treatment adherence